„Valsts sagrābšanas” koncepts: Latvijas piemērs - Ansonska, Evija (Latvijas Universitāte, 2007)
“Valsts sagrābšanas” koncepts: Latvijas piemērs Anotācija Pasaules Banka 2000.gada pētījumā par korupciju bijušajā komunisma valstīs, Austrumeiropā un PSRS pirmo reizi politiskās korupcijas definēšanai šajā reģionā lietoja terminu “valsts sagrābšana” Vienlaikus PB savos pētījumos konstatēja, ka lielākā daļa pospadomju valstu, tai skaitā Latvija ir smagas politiskās korupcijas skarta. PB konstatēto, ka Latvijas “valsts ir sagrābta” un tās svarīgākās valsts institūcijas pārņemtas, nākamos gados apstiprināja arī virkne citu autoritatīvu starptautisko un Latvijas ekspertu veiktie pētījumi, tādejādi neapstrīdami apliecinot problēmas politisko nozīmību ne tikai atsevišķās valstīs, bet reģionā kopumā. Arī Latvijas piemēra analīze apliecina, ka, neskatoties, ka no Latvijas neatkarības atjaunošanas pagājuši jau padsmit gadi, joprojām var runāt par plaša mēroga politisko korupciju, turklāt līdz ar gadiem korupcijas apjomam nebūt nav tendence samazināties, bet gan pieaugt, iegūstot arvien rafinētākas un grūtāk identificējamas formas. Kā klaiskākos Latvijas “valsts sagrābšanas” piemērus var minēt Latvenergo “trīs miljonu lietu”, valsts digitālās televīzijas ieviešanas projektu, politiķu un partiju parakstītos sadarbības līgumus par noteiktas politikas realizāciju un lavēlīgu lēmumu pieņmšanu, Aivara Lemberga krimināllietu, Jūrmalgeitas skandālu, vēlēšanu kampaņu tēriņu ierobešojumu neievērošana, ar valsts drošības dienestiem saistīto likumu grozīšana u.c. Līdz ar virkni iepriekš minētajiem koruptīvajiem darījumiem un aizdomām par rafinētu “valsts institūciju sagrābšanas” realizāciju, ir pamats apgalvot, ka pēdējo 17 gadu laikā Latvijā ir notikusi arī ekonomiskās un politiskās varas saplūšana un atsevišķu politisko spēku biznesa un politisko interešu izlīdzināšanās jeb vienādošanās, ko lielā mērā sekmējus kvazi-politisku organizāciju darbība Latvijā. Tāpēc darbs “Valsts sagrābšanas” koncepts: Latvijas piemērs skaidro un risina aktuālas mūsdienu Latvijas politikas jautājumu, piedāvājot politisko korupciju skatīt caur politisko partiju prizmu.

“State Capture” concept: Latvia case study Synopsis In 2000, the World Bank in its research about corruption in post-Soviet region – Eastern Europe and USSR – for the first time subdivided corruption not according its scope, but according its type into administrative and political corruption, defining it as “state capture” At the same time the World Bank revealed in its researches that most of post Soviet countries including also Latvia are affected by hard political corruption defined as “state capture”. What was stated by the World Bank that Latvian “state is captured” and its most important state institutions seized, a year later was confirmed also by UN Development Programme’s National Human Development Report for Latvia published in 2001 and analyzing decision making mechanisms and procedures in the country. Key conclusion of the report was that a closed model of politics formation had developed in Latvia, where parties and business elite have decisive importance, while civic society has trifling influence on political process. These and similar conclusions were confirmed also in other international and local researches about Latvia. Analysis of the Latvia’s case also confirms that although 17 years passed since the independence of Latvia had been restored we still can talk about wide-scale political corruption. Moreover, with the course of time corruption tends not to diminish but expand, becoming even more refined and complicated for identification. Among classical examples of “state capture” over the last years we can mention Latvenergo “three million case”, state project for digital TV launch, agreements between politicians and parties about the implementation of fixed policy and adoption of favourable decisions, Aivars Lembergs’ criminal case, Jūrmalgeit scandal, non-observance of expenses limit for election campaigns, amendments to laws regarding national security services etc. All above mentioned corruption cases and suspicions about refined “state institutions capture” being realized, suggest that over past 17 years economic and political powers have merged in Latvia and business and political interests of some political forces have equalized or unified, which was very much promoted by the activity of quasi-political organizations in Latvia. The goal of this study was to make analysis of most wide-scale Latvia’s cases of “state capture”, which confirm seizure of most important state institutions – legislative and executive power, by using the World Bank’s concept of “state capture”, corruption typology suggested by political scientist Rasma Kārkliņa and Transparency International. At the same time another task of the study was to prove a hypothetic assertion about the importance of quasi-political organisations in seizing state institutions and to describe the mechanism of merger between economic and political powers. Principles of quasi-political organisation formation and activity were described using the example of the People’s Party and Latvia’s First Party. The study concluded that the seizure of most important Latvian state institutions realized by secret powers network in the nineties of the 20th century guaranteed political elite a possibility to fulfil its interests avoiding possible penalty. There are also reasons to suspect that legislation has been „arranged” appropriately by misusing power with the aim to fulfil personal or sponsors’ economic interests and neutralize political or business competitors. The cases analyzed in the study also confirm that political agenda of political parties, government and parliament differs very much from people’s political agenda. Over these years it was one of the crucial factors, which furthered people’s estrangement from the state authorities and distrust to them. Thus we can forecast that also Latvian society will soon run out of patience with such all embracing corruption, because as V.Kalniņš points out, there are at least two further alter
„State capture” concept: Latvia case study
Keywords: Politikas zinātne (politoloģija)